Hydrology Analysis and Modelling for Klang River Basin Flood Hazard Map - Sidek L.M.; Rostam N.E.; Hidayah B.; Roseli Z.A.; Majid W.H.A.W.A.; Zahari N.Z.; Salleh S.H.M.; Ahmad R.D.R.; Ahmad M.N. (Institute of Physics Publishing, 2023)
Climate change; Developing countries; Hazards; Hydrology; Analysis and modelling; Environmental hazards; Flood hazard maps; Flood prone area; Hydraulic parts; Impact of floods; River basins; Floods; climate change; developing world; environmental hazard; flooding; hazard assessment; hydrological modeling; runoff; urbanization; Klang Basin; Malaysia; Selangor; West Malaysia